Стадії дисциплінарного провадження в органах Національної поліції щодо притягнення до дисциплінарної відповідальності - Шевченко, О. О.; Shevchenko, О. О. (Юридичний науковий електронний журнал. - 2020. - № 5. - С. 171-174, 2020)
Досліджено наукові позиції вчених щодо виокремлення стадій дисциплінарного провадження в правоохоронних органах та їх особливості. Під стадіями дисциплінарного провадження в органах Національної поліції щодо притягнення до дисциплінарної відповідальності запропоновано розуміти врегульований адміністративно-процедурними нормами комплекс здійснення відносно самостійних, логічно пов’язаних процесуальних дій, спрямованих на виконання власних завдань у межах дисциплінарного провадження щодо розв’язання дисциплінарної справи шляхом прийняття та реалізації процесуального рішення в чітко визначений законодавством строк. Доведено, що кожна стадія дисциплінарного провадження має свою специфіку, самостійну мету здійснення, процесуальний акт, якими фіксується початок і закінчення стадії.

The article examines the scientific positions of scientists on the separation of stages of disciplinary proceedings in law enforcement agencies and their features. Under the stages of disciplinary proceedings in the National Police to bring to disciplinary responsibility, it is proposed to understand the procedure regulated by administrative and procedural norms for independent, logically related procedural actions aimed at fulfilling their tasks within disciplinary proceedings to resolve and resolve disciplinary cases by adoption and implementation of a procedural decision within a period clearly defined by law. Direct appeal to the Disciplinary Statute of the National Police of Ukraine provided an opportunity to identify the following stages of disciplinary proceedings in the National Police to bring a police officer to disciplinary responsibility, namely: 1) stage of official investigation disciplinary misconduct, or direct detection of signs of such misconduct by a police official in the presence of sufficient data indicating signs of disciplinary misconduct); 2) consideration of the case of disciplinary misconduct and decision-making; 3) execution of the decision based on the results of the disciplinary case. The article proves that the stage of appealing the decision to apply disciplinary measures is an independent type of proceedings, because within this proceeding a specific task is solved for this type of proceedings, we have a corresponding range of subjects of proceedings, as well as a set of consistent legal actions. take place within a certain time frame and ultimately a decision is made on the case. It is proved that each stage of disciplinary proceedings in the bodies of the National Police has its own specifics, independent purpose of implementation, procedural act, which fixes the beginning and end of the stage.

Исследованы научные позиции ученых по выделению стадий дисциплинарного производства в правоохранительных органах и их особенности. Под стадиями дисциплинарного производства в органах Национальной полиции по привлечению к дисциплинарной ответственности предложено понимать урегулированный административно-процедурными нормами комплекс осуществления относительно самостоятельных, логически связанных процессуальных действий, направленных на выполнение собственных задач в рамках дисциплинарного производства по решению дисциплинарного дела путем принятия и реализации процессуального решения в четко определенный законодательством срок. Доказано, что каждая стадия дисциплинарного производства имеет свою специфику, самостоятельную цель осуществления, процессуальный акт, которым фиксируется начало и окончание стадии.
Stages of disciplinary proceedings in the bodies of the National Police regarding disciplinary responsibility
Шевченко, О. О. Стадії дисциплінарного провадження в органах Національної поліції щодо притягнення до дисциплінарної відповідальності [Електронний ресурс] / Шевченко О. О. // Юридичний науковий електронний журнал. - 2020. - № 5. - С. 171-174. - Режим доступу: http://lsej.org.ua/5_2020/42.pdf.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; дисциплінарне провадження; disciplinary proceedings; дисциплинарное производство; дисциплінарна відповідальність; disciplinary responsibility; дисциплинарная ответственность; стадії дисциплінарного провадження; stages of disciplinary proceedings; стадии дисциплинарного производства; дисциплінарна справа; disciplinary case; дисциплинарное дело; службове розслідування; official investigation; служебное расследование